Unmasking Xenophobia: Exploring Anti-Chinese Sentiments in Indonesia through a Criminological Lens - Eko Nurisman; Antony Antony (Universitas Internasional Batam, 2023)
The Chinese ethnicity in Indonesia has traversed a long and intricate historical journey, grappling with the quest for identity and nationality as Indonesian citizens. Despite the attempts to deny or overlook this reality, the truth remains steadfast: Indonesian Chinese individuals cannot evade racism and social envy in their day-to-day lives as citizens of Indonesia. In certain instances, this even manifests as symptoms of xenophobia, an excessive disdain or prejudice towards those perceived as foreigners. This research delves into the symptoms of xenophobia experienced by the Indonesian Chinese, meticulously recounting past occurrences while exploring the public's endeavors to uphold Indonesia's ideology of Pancasila as a unifying force. By employing a statutory, conceptual, and historical approach, this study reveals that xenophobia towards the Indonesian Chinese community has persistently plagued the public consciousness, despite their legal recognition in the country. The protection of Indonesian Chinese necessitates the establishment of specialized legal instruments. Furthermore, alongside regulating their protection, the maximization of efforts lies in embracing Pancasila as a powerful instrument of national unity.